Adverse skin reactions to personal protective equipment during COVID‐19 pandemic in Italian health care workers. Issue 6 (23rd March 2022) - Proietti, Ilaria; Borrelli, Ivan; Skroza, Nevena; Santoro, Paolo Emilio; Gualano, Maria Rosaria; Bernardini, Nicoletta; Mambrin, Alessandra; Tolino, Ersilia; Marchesiello, Anna; Marraffa, Federica; Michelini, Simone; Rossi, Giovanni; et al.
Abstract: To avoid exposure to SARS‐COV‐2, healthcare professionals must use personal protective equipment (PPE). Their use has been related to a series of adverse effects; the most frequent adverse events were headache, dyspnoea, and pressure injuries. Skin adverse effects are very common, including contact dermatitis, itching, erythema, and acneiform eruptions. The objective of this study is to evaluate the skin problems caused by personal protection equipment (PPE) in health care workers (HCWs) and to individuate eventual risk factors. From May to June 2020 a retrospective observational multi‐centric study conducted by an online survey sent by email, involving 10 hospital centers, was performed. We considered as independent variables gender and age, occupational group and sector, time of utilization, type and material of PPE. We tested 3 types of PPE: gloves, bonnet, and mask for different time of utilization (<1, 1–3, 3–6, >6 h). We performed a multiple logistic regression model to correlate them with skin adverse events occurrence. Among all the 1184 participants, 292 workers reported a dermatological pathology: 45 (15.41%) had psoriasis, 54 (18.49%) eczema, 38 (13.01%) acne, 48 (16.44%) seborrheic dermatitis, and 107 (36.64%) other. In our sample previous inflammatory dermatological conditions, female sex, prolonged use of PPE were significant risk factors for developing skin related adverse events considering all the PPE considered. The use of PPE is still mandatory in the hospital setting and skin adverse reactions still represent a global problem. Although data from Europe are limited, our study highlighted the importance of the problem of PPE skin reactions in a large sample of Italian healthcare professionals.